2007
DOI: 10.1371/journal.pone.0000855
|View full text |Cite
|
Sign up to set email alerts
|

Is Transcriptional Regulation of Metabolic Pathways an Optimal Strategy for Fitness?

Abstract: BackgroundTranscriptional regulation of the genes in metabolic pathways is a highly successful strategy, which is virtually universal in microorganisms. The lac operon of E. coli is but one example of how enzyme and transporter production can be made conditional on the presence of a nutrient to catabolize.MethodologyWith a minimalist model of metabolism, cell growth and transcriptional regulation in a microorganism, we explore how the interaction between environmental conditions and gene regulation set the gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…Thus the metabolic activity which is linked to substrate uptake rate fell only after 4 hours post-induction. The down-regulation of energy generating pathways also leads to a drop in growth rate ( Kasimoglu et al 1996 ; Troein et al 2007 ) which was also observed in the present case. It has been previously reported that in complex medium, several genes of energy generating pathways such as hycB, cyoA, cydA, and ndh , were down-regulated, along with the ATP synthase gene ( Oh and Liao 2000 ), which is similar to our observations.…”
Section: Discussionsupporting
confidence: 86%
“…Thus the metabolic activity which is linked to substrate uptake rate fell only after 4 hours post-induction. The down-regulation of energy generating pathways also leads to a drop in growth rate ( Kasimoglu et al 1996 ; Troein et al 2007 ) which was also observed in the present case. It has been previously reported that in complex medium, several genes of energy generating pathways such as hycB, cyoA, cydA, and ndh , were down-regulated, along with the ATP synthase gene ( Oh and Liao 2000 ), which is similar to our observations.…”
Section: Discussionsupporting
confidence: 86%
“…In addition, the non-optimized expression of enzyme genes may facilitate the accumulation of toxic intermediate metabolites, which decreases the production yield. To resolve this problem, promoters with different strengths are widely employed to fine-tune the expression levels of enzyme genes [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although these two main modeling frameworks are well-adapted to determine optimal flux balance in detailed metabolic reaction networks, they remain dependent on steady-state or quasi-steady-state assumptions or on small perturbation approximations. A third approach consists in using simplified models depicting generic motifs (unbranched or cyclic pathways) or a prototypical metabolism, which allows studying regulation in simple resource allocation problem such as the switch from one to another substrate [ 29 , 30 ], the switch between respiratory and fermentation metabolism [ 31 ], or the evolution of regulatory complexity [ 32 ]. The total number of kinetic parameters in these models is usually low enough to allow for extensive parameter space exploration or for parameter optimization through evolutionary computation techniques, without necessarily requiring additional assumptions of steady state or of small enough environmental fluctuations.…”
Section: Introductionmentioning
confidence: 99%